"The whole experience is still very high touch for parents": Parent moves to support young children's remote learning during the COVID-19 pandemic. (December 2022) - Carrell Moore, Holly
This qualitative study examined families' experiences supporting young children's (ages 3–8) remote learning during the COVID-19 pandemic. Twenty-three participants completed open-ended questions in an online survey and three of those participants shared further in an online, recorded focus-group interview. Parents revealed young children's challenges with remote learning and the multiple strategies families took up to support their young learners, including many forms of managing and facilitating online work, several forms of communicating to seek support, information, or changes, and multiple forms of motivating their child(ren) to stay engaged and complete activities. Parents also shared the tensions that arose with more unfettered access to their child(ren)'s online classrooms, teachers' variation in communication, and families differing levels of participation due to multiple responsibilities. The findings demonstrate both the challenges and families' creative strategies to bolster their child(ren)'s remote learning, and they inform teachers and school personnel of the importance of developing continued recalibration of communication, family support, and family input on home learning experiences when young children cannot engage with in-person learning.